American Radicalism. Issue 1 (20th April 2017) - Foner, Eric
Abstract: Twenty years after his death, Raphael Samuel's book Theatres of Memory remains essential reading for those interested in the nature of historical memory. Rarely, either among historians or journalists, does the discussion achieve the interpretive sophistication, the sympathetic understanding of how memory is constructed, or the insight into the connections between popular and official memory evident in Samuel's book. Samuel also inspired research into the history of radicalism, a subject that, in the United States, has taken on renewed importance given the surprising success of the Bernie Sanders campaign in 2016. Having taught a course on the Radical Tradition in America as Sanders was seeking the Democratic nomination, I was struck by how the collapse of neoliberalism due to the financial crisis of 2008 and recent movements such as Occupy Wall Street and Black Lives Matter have led a generation of young Americans to think in new ways about social change. Historians of radicalism, and historians who consider themselves radicals, need to follow Samuel's lead in using history as a critical lens for understanding society and pointing the way to a better future.